Leveraging neuroleadership and adopting AI to improve human capital development in IT&C business organisations - Roxana-Maria Stăneiu; Mădălina-Elena Stratone; Dan Cristian Dabija; Pompei Mititean (Amfiteatru Economic, 2024)
This paper aims to explore how business organisations in the Romanian IT&C sector strategically implement neuro-leadership principles to accelerate the adoption and implementation of artificial intelligence (AI) technologies, thus enhancing human capital development and promoting sustainable competitive advantages. Applying the focus group method, dynamic discussions were held with 10 representatives of Romanian IT&C companies to highlight how these business organisations strategically implement neuro-leadership principles and adopt AI technologies in human capital management. The results of the research, divided into four main themes, reveal the importance of neuroleadership in improving employee competencies as well as overcoming the challenges associated with implementing AI in organisations. Research provides new and relevant insights for leaders in business organisations to effectively adapt to the complexity of technological change caused by AI adoption in human resource management. At the same time, the results reveal the importance of fostering a culture of continuous learning and development to harness the potential benefits of AI, while mitigating the risks associated with this approach. The originality of the paper is derived from the merging of the fields of leadership, neuroscience, and AI, thus providing a comprehensive understanding of the dynamics shaping organisational responses to technological innovation. The research addresses a notable gap in the literature by exploring concrete strategies to accelerate AI adoption through neuroleadership principles, enriching the literature on this multidimensional relationship.
Keywords: O32; J24; D83; D84; 330; neuro-leadership; neuro-leaders; human capital; artificial intelligence (AI); artificial intelligence technologies; employees; and business organisations